Imaginary Worlds: Plural Seas, Liminal Foundations, Contested Identities - James Louis Smith (Bloomsbury Publishing Plc, 2022)
A Cultural History of the Sea in the Medieval Age, ed. by Elizabeth Lambourn. The cultural history of the sea during the Middle Ages is a young and dynamic field. Born only recently in the literary criticism of European sources, this innovative volume pushes out beyond this European heartland to explore the shape and potential of a cultural history of the sea constructed also from global literatures and oral traditions, and from material things. The chapters in this volume bring together the perspectives and expertise of archaeologists, historians and literary historians with a core focus on Afro-Eurasia and its encircling seas. Topics explored include: the evolving visual representation of the seas in Europe, the Islamic world and the Far East; the development of navigation technologies in the seas around Afro-Eurasia; imaginative projections of the sea in cultures ranging from Maori Aotearoa to Europe; a history of maritime and riverine trade networks across medieval Afro-Eurasia and two novel comparative studies, of islands and shores in Mediterranean and Indian Ocean history, and of the archaeology of fishing and fish eating in the North Atlantic and Swahili worlds. This volume does not pretend to offer a definitive answer to how a more global cultural history of the sea should be written; it offers not 'The' but 'A' Cultural History of the Sea for the period between 800 and 1450 CE, shaped as much by the parameters of the series itself as by the vision, curiosity and expertise of its editor and individual contributors. In so doing this volume hopes to open fresh dialogues amongst cultural historians of the sea and bring new ideas and questions to the greater numbers of non-specialists just now venturing into this field.